The multinational firm and international trade policy - Arye L. Hillman; Heinrich W. Ursprung (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1989)
This paper examines the relation between the multinational firm and the determination of international trade policy. At issue is whether the multinational firm exerts a protectionist or liberalizing influence on countries' national trade policies. Vertical integration appears quite unambivalently to give the multinational firm reason to favor liberal international trade policies. Horizontally integrated multinational enterprises, on the other hand, are inherently more protectionist than national firms since they own local import-competing production facilities at home and abroad, and hence have an interest in protection in both markets. Such protectionist presumption notwithstanding, we nevertheless demonstrate that via the process of political competition the horizontally integrated multinational enterprise has a liberalizing influence on the determination of countries' international trade policies.
Keywords: 330